Extubation outcomes in critically ill post-craniotomy patients: A retrospective cohort study - Jianfang Zhou; Xu-Ying Luo; Guangzhi Shi; Hong-Liang Li; Guang-Qiang Chen (PLoS ONE, 2025)
Objective Extubation failure is common in critically ill post-craniotomy patients. This study aimed to assess extubation outcomes and examine demographic and surgical predictors of extubation success. Methods In this retrospective cohort study, we analyzed adult ICU patients from January 2017 to December 2020 with ≥24 hours of both ICU stay and endotracheal intubation. We collected demographic characteristics, surgical parameters, severity scores (APACHE II, SOFA, GCS), and extubation outcomes. Independent predictors of successful extubation were determined through multivariate logistic regression. Results Among 1,683 enrolled patients, first-attempt extubation success was achieved in 70.7% (1,190/1,683), declining to 46.6% (135/290) and 28.6% (12/42) for second and third attempts respectively. Subsequent tracheostomy was performed in 19, 3, and 1 patients following first, second, and third successful extubations. At discharge, 1,244 patients (73.9%) maintained extubation success while 348 (20.7%) required tracheostomy. Successful first extubation correlated with significantly reduced ICU stay (median 4 vs 15 days, p < 0.001) and total hospitalization duration (19 vs 30 days, p < 0.001), though mortality rates showed no significant difference (6.0% vs 8.1%, p = 0.106). Multivariable analysis demonstrated that male sex (OR 0.680, 95% CI 0.531–0.871), history of hypertension (OR 0.637, 95% CI 0.489–0.829), supratentorial lesions (OR 1.315, 95% CI 1.016–1.701), SOFA score (OR 0.844, 95% CI 0.791–0.900), and APACHE II score (OR 0.930, 95% CI 0.902–0.958) were independent factors influencing initial extubation success. Conclusion Although first-attempt extubation success remains suboptimal in post-craniotomy critical care, nearly half of initial failures achieve success on subsequent attempts. Multivariable analysis identified female sex, absence of hypertension, infratentorial lesions, lower SOFA, and APACHE II score were independent predictors of initial extubation success.